THU0028 Interstitial Lung Disease in Primary SjÖGren Syndrome: A Gessar Analisys. (10th June 2014) - Velez, S.D.; Zazzetti, F.; Galván, L.S.; Gallacher, A.; Mayer, M.; Rivero, M.; Gomez, A.; Marina, K.C.; Duartes Noè, D.; Busamia, B.; Caeiro, F.; Encinas, L.; et al.
Abstract : Background: Interstitial lung disease (ILD) in primary Sjögren Syndrome (pSS) includes Non Specific Interstitial Pneumonia (NSIP), Usual Interstitial Pneumonia (UIP), Lymphocytic interstitial pneumonia (LIP) and Organized Pneumonia (OP), all related to poor outcome. The existing frequency of ILD is unknown in Argentina. Objectives: To describe the frequency of ILD in pSS using the Argentinean Group of Study for Sjögren Syndrome (GESSAR) database and to identify the associated features of the disease. Methods: GESSAR database included 374 patients who fulfilled the 2002 criteria for pSS. The diagnosis of ILD was based on High Resolution Chest Computed Tomography (CT) according to the American-European Consensus for ILD. A control/case analysis was performed including patients with (cases) and without ILD (controls) with a 4:1 ratio. Mann-Whitney was employed for numeric variables and chi square or fisher's test for categorical variables. A p<0.05 was considered statistically significant. Results: Of the 374 patients analyzed, 95% were women. Mean age at inclusion was 55, 67 (range 25-83) and 51, 07 (range 21-80) at diagnosis. The frequency of ILD was 6, 41% (24/374). Mean age at inclusion was 61, 91 (range 51-72) and 52.2 at diagnosis (range 34-69). NSIP was found in 75%, followed by UIP in 20, 2% and OP in 4, 8%. Ground glass opacities: 87, 5%, honeycombing: 20% (2 patients had both). FEV1 and FVC were below predicted values in 58, 3% and 54, 1% respectively. DLCO was done in 66, 6%, with a mean value of 64, 6% and 80, 2% when DLCO was corrected with VA. Patients with ILD more frequently showed sialoadenitis (28%), purpura (16, 6%), Raynaud's (20, 8%), non-erosive arthritis (41%), polyclonal hypergammaglobulinemia (41%), hypocomplementemia (29%), leucopenia (28%), cryoglobulinemia (4, 1%), PBC (4, 5%), anti-Ro/SSA (80%), urticarial vasculitis (4, 7%) and glomerulonephritis (9, 52%). After case/control comparison, only glomerulonephritis reached statistical significance (p=0.042). Conclusions: Although the frequency of ILD was characteristically low in our cohort, NSIP was the most frequent. A significant correlation was found between those patients with ILD and glomerulonephritis. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.2619